'It was all in your voice' - Tertiary student perceptions of alternative feedback modes (audio, video, podcast, and screencast): A qualitative literature review. (January 2019) - Killingback, Clare; Ahmed, Osman; Williams, Jonathan
Abstract: Background: Feedback is an integral part of teaching and learning with written comments being one of the most widely used methods of providing student feedback. From the student perspective, written feedback has been seen as limited in terms of its quality, vague nature and lack of clear examples with feed-forward. Alternative feedback modes (including audio, video, podcasts, and screencast feedback) have been suggested as a means of enhancing feedback. Objective: The purpose of this qualitative literature review is to synthesise the views of tertiary students on alternative feedback modes. Review methods: Searches were carried out in five online scientific databases (ERIC, Education Source, PsycINFO, Teacher Reference Center, and CINAHL Complete). Potentially relevant studies were screened against the inclusion/exclusion criteria. Data were extracted using customised data extraction forms. The qualitative findings section of each included study underwent thematic synthesis. Results: A total of 450 studies were identified through the search strategy. Ten studies met the inclusion criteria. Five themes were identified: belonging; greater comprehension from non-verbal aspects of communication; individualised and personal; technical/practical technology aspects; and circumstances and context. Conclusion: Alternative feedback modes help students achieve a greater level of comprehension of feedback, with feedback that was more personalised. The alternative feedback modes promote a sense of belonging in relation to the programme of study and in relation to teaching staff. Educators should consider the use of innovative media approaches which could enhance and improve the quality of the student feedback experience.